احکام ِشرعیہ میں تبدیلی کے اصول و ضوابطPrinciples for Change in Sharīʻa Rules (Al-Qamar, 2021)
Evidence of exceptions in circumstances and time from the Quran, because the Quran itself has been revealed in 23 years.  Yes it has been proved that the rules of sharia have the capacity to deal the changing circumstances, but whether the change in circumstance will cause any change in the sharia rules completely or some part of the sharia rules, and if what are the rules and regulations for the changing rules of sharia, if era accept change due to change of time, so what are the rules regulations for them and which change possible in sharia rules. Therefore, in this article which under discussion, are explain these rules and principles for Changing the rules of sharia.
Keywords: Sharīʻah rules; change; Principles